Analisis Perbandingan Literasi Keuangan Dalam Pengambilan Keputusan Berinvestasi Bagi Guru Bersertifikasi dan Guru yang Tidak Bersertifikasi - Riskiyah, Fadilatul; Septiana, Aldila (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the differences in financial literacy levels and their influence on investment decision making between certified and uncertified teachers in Bangkalan Regency. Financial literacy is an important aspect in supporting individuals to make smart investment decisions, especially for teachers who have limited income and access to financial information. This study uses a quantitative approach with a survey method by distributing questionnaires to 50 respondents, consisting of 41 certified teachers and 9 uncertified teachers. Data analysis techniques used include validity, reliability, normality, determination coefficient (R²), t-test, and f-test, with the help of the SPSS 25 program. The results of this study indicate that financial literacy has a significant effect on investment decision making, both for certified and uncertified teachers. However, the influence is stronger for uncertified teachers (R² = 81%) compared to certified teachers (R² = 36.3%). These findings indicate that improving financial literacy is very important for all groups of teachers, especially for those who do not have access to formal training. Therefore, it is recommended that there be a financial literacy program that is evenly distributed and sustainable to improve the quality of personal financial management among educators.